2023
DOI: 10.1161/hypertensionaha.122.18550
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Hypertension: The Impact of Earlier Life Challenges: Excellence Award for Hypertension Research 2021

Abstract: Hypertension affects over 1 billion individuals worldwide. Because the cause of hypertension is known only in a small fraction of patients, most individuals with high blood pressure are diagnosed as having essential hypertension. Elevated sympathetic nervous system activity has been identified in a large portion of hypertensive patients. However, the root cause for this sympathetic overdrive is unknown. A more complete understanding of the breadth of the functional capabilities of the sympathetic nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…First, an initial increase in pressure is associated with an ANGII-mediated systemic vasoconstriction. Then, this phase is replaced by a second, long-term, neurogenic component [ 9 , 24 , 25 ]. In the present studies, the initial increase in BP response to systemic ANG II administration during the first week was comparable between rats pretreated with S1 protein and rats pretreated with VEH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, an initial increase in pressure is associated with an ANGII-mediated systemic vasoconstriction. Then, this phase is replaced by a second, long-term, neurogenic component [ 9 , 24 , 25 ]. In the present studies, the initial increase in BP response to systemic ANG II administration during the first week was comparable between rats pretreated with S1 protein and rats pretreated with VEH.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been established from both animal and human studies that excessive activation of the sympathetic nervous system plays a primary role in the development and progression of the essential hypertension [ 7 9 ]. Inflammation and oxidative stress in the brain, particularly in the hypothalamic paraventricular nucleus (PVN), a cardiovascular regulatory center in the brain that integrates neural and humoral signals driving the sympathetic nervous system, are key factors in regulating sympathetic nerve activity and blood pressure [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using microarrays, hypothalamus-specific genes contributing to the hypertension phenotype were determined, and certain genes that were upregulated >2-fold in developmental origins of health and disease rat models were identified. Pathway analysis revealed that the angiotensin signaling pathway, an important central mechanism regulating sympathetic nerve activity and cardiovascular function, 23 was one of the top-ranked pathways. Consistently, the mRNA expression of angiotensin receptor AT1A in the hypothalamic paraventricular nucleus was significantly higher in low-protein offspring than in normal-protein offspring.…”
Section: Prenatal Programminghypertensionmentioning
confidence: 99%
“…Comorbidities were diagnosed as previous publications described. [29][30][31][32] Hypertension was defined as repeated SBP ≥ 140 and/or DBP ≥ 90 mmHg or ongoing anti-hypertensive medications. Diabetes mellitus was diagnosed when FBG ≥ 7.0 mmol/L, 2-h plasma glucose ≥ 11.1 mmol/L, or current consumption of hypoglycemic drugs.…”
Section: Introductionmentioning
confidence: 99%